Design and development of a mitochondrial-targeted photosensitizer for two-photon fluorescence imaging and photodynamic therapy. (1st April 2023) - Chen, Yu; Zhang, Sheng; Cheng, Tianjiao; Lin, Wei; Mao, Linlin; Chen, Zhonghui; Yang, Yang; Huang, Hanqing; Li, Jinqiu; Ke, Zhiyong; Cui, Zhong-Kai
Highlights: A rationally designed mitochondrial-targeted photosensitizer, TTTP, for PDT. TTTP can track living cells in vitro and in vivo by two-photon fluorescence imaging. TTTP shows selective cytotoxicity to cancer cells, particularly under irradiation. TTTP stimulates ROS in mitochondria, activating apoptosis to inhibit tumor growth. Abstract: Mitochondria are well-acknowledged as ideal targets for tumor therapy due to their important role in energy supply and cellular signal regulation. Mitochondria-specific photosensitizers have been reported to be critical for inducing cell apoptosis. Two-photon fluorescence imaging provides a new technique for delineating biological structures and activities in deep tissues. Herein, we developed a new aggregation-induced emission (AIE) active photosensitizer by attaching a pyridinium group for mitochondrial targeting. The rationally designed photosensitizer (TTTP) exhibited excellent photophysical properties, good biocompatibility, reactive oxygen species (ROS) stimulation ability, anticancer efficacy, and two-photon imaging properties. TTTP was highly taken up by cells and accumulated specifically in mitochondria but was selectively cytotoxic to cancer cells. Under light irradiation, the generation of ROS was significantly boosted, leading to actively induced apoptosis. The in vivo tumor photodynamic therapeutic efficacy of TTTP showed significant inhibition of tumor growth. Furthermore, the underlying mechanism of TTTP tumor suppression revealed that the apoptosis agonist Bax was markedly up-regulated while the antagonist Bcl-xL was down-regulated. This research provides a potential mitochondrial-targeted phototherapeutic agent for effective therapy and two-photon fluorescence imaging.